An unusual case of myopic shift post acquired brain injury - Sunderji, Farrah F; Heyman, Catherine (Canadian Journal of Optometry, 2012)
Background Ocular and visual problems are frequent consequences of an acquired brain injury (ABI). The literature suggests that many patients demonstrate a myopic shift in refractive error after a traumatic brain injury (TBI), a form of an ABI. Three reported courses are suggested. Most commonly the myopia resolves under cycloplegic conditions, secondly the shift is transient, and least commonly the myopia increases over time. This case report, although not due to a TBI, is an example of the least common subgroup. Case Report The patient, a 63 year-old male, presented with a history (15 months prior to initial evaluation) of an excised right frontal temporal lobe tumour. The history included dexamethasone 4mg QD pre- and post-surgery which caused blood glucose levels to fluctuate between 5.72-22.2 mmol/l; a stroke occured postsurgery causing hemiparesis on his left side; and shunt surgery to decrease swelling to the area of excision and the optic nerves. Medications included: Cartia, lisinopril, Toprol XL, prednisone, Reglan, and Temodar. The patient was receiving chemotherapy to treat remnants of the tumour. His last eye exam in 2004 indicated a refractive error of -2.50-1.25X080 in his right eye and -3.000.75X080 in his left eye with visual acuity of 6/7.5 in both the right and left eye. He presented to our clinic with an aided visual acuity of 8/100 (6/110) in both the right and left eye and a left homonymous hemianopsia on finger counting fields. Cycloplegic retinoscopy revealed -6.003.00X090 in his right eye and -6.002.00X090 in his left eye. Dilated fundus exam showed mild swelling of both optic nerves. The patient reported blood glucose levels of 103-140. At a one-month follow-up, his best corrected visual acuity at a distance improved to 6/60 in both the right and left eye through the new prescription. His cycloplegic retinoscopy did not show any change in myopia or astigmatism and the disk edema was resolved. Conclusion This case illustrates an unusual presentation of myopic shift post ABI. The patient’s condition continued to deteriorate eventually taking his life. It remains unclear whether the myopia and astigmatism continued to increase or remained stable. Although, the cause of this change is not fully understood and needs further investigation, providing appropriate optical correction did improve the patient’s quality-of-life.